Optimalisasi Pendayagunaan Pekarangan untuk Mewujudkan Ketahanan Pangan Petani Lahan Kering di Desa Rembitan Kabupaten Lombok Tengah - Dewi, Ika Nurani; Utami, Septiana Dwi; Primawati, Sri Nopita; Jannah, Husnul; Sumarjan, Sumarjan (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2022)
Most of the agricultural land in Rembitan Village is dry land with food productivity dominated by corn. This condition has an impact on the low consumption of food and community nutrition, and can threaten household food security. By optimizing the use of yard land, it is expected to increase food independence and meet the food and nutritional needs of the family. The purpose of this community service activity is to increase the knowledge and skills of farmers through the transfer of innovation and cultivation technology in their yards to realize food independence and fulfill family nutritional needs. This service activity was carried out in March 2022. The implementation of the training used a participatory approach method. This community service activity was considered quite successful, seen from the enthusiasm and perseverance of the participants in participating in counseling activities, as well as interest in implementing effective planting patterns in the use of the yard. Continuous assistance from all parties, especially the local government, is highly expected to increase food availability and household food self-sufficiency, especially for dry land farmers.